Grammar and Utility Functions of Pronouns - Tulaboeva Gulorom Tulaboevna (Genius Journals, 2022)
The question of pronouns is of considerable interest to any language. The peculiar nature of these words has always attracted the attention of researchers, and we find in the literature many works devoted to the description of pronouns. However, these works are for the most part relevant sections of scientific grammars of a particular language, devoted to individual issues related to pronouns.
Keywords: subject; speech; concept; object and attribute